High Strain Sensitivity Temperature Sensor Based on a Secondary Modulated Tapered Long Period Fiber Grating - Xiren Jin; Cuiting Sun; Shujie Duan; Weiliang Liu; Guoan Li; Shuo Zhang; Xudong Chen; Lei Zhao; Chunlian Lu; Xinghua Yang; Tao Geng; Weimin Sun; et al. (IEEE Photonics Journal)
A novel sensor structure has been proposed and experimentally investigated for simultaneous strain and temperature measurement. The structure is fabricated by weak power modulation of CO2 laser exposure on tapered long period fiber grating (LPFG). Compared with the transmission spectrum of the tapered LPFG, two peaks appear in the transmission spectrum of the novel structure. These resonance peaks exhibit different sensitivity responses; thus, simultaneous measurement of strain and temperature is realized by monitoring the wavelength shift of the two peaks. Experiment results indicate that strain sensitivities of the two peaks are 1.82 pm/μϵ and 8.17 pm/μϵ, and temperature sensitivities are 47.9 pm/°C and 65 pm/°C, respectively.